Avoiding abnormal grain growth when annealing selective laser melted pure titanium by promoting nucleation. (1st March 2022) - Chen, Kewei; Huang, De Jun; Li, Hua; Jia, Ning; Chong, Warren
Abstract: In this study, the recrystallization process of selective laser melted (SLM) commercially pure titanium (CP-Ti) was followed by a quasi-in-situ electron backscatter diffraction (EBSD) method at 800 °C and 700 °C. Abnormal grain growth (AGG) initially emerges at the beginning of annealing at 800 °C and is primarily caused by strain-induced boundary migration (SIBM). However, at the beginning of annealing at 700 °C, many small equiaxed grains are formed due to more recrystallization nucleation, followed by the formation of AGG resulting from the secondary recrystallization. Based on these findings, appropriate control of the annealing time at 700 °C can mitigate AGG to obtain fine equiaxed grains with weak texture to enhance the tensile properties of SLM CP-Ti. Graphical abstract: Image, graphical abstract